UNVEILING THE INFLUENCE OF SOCIAL MEDIA ON SOCIAL MOVEMENTS: ANALYZATION, MOBILIZATION, ORGANIZATION, AND OUTCOMES THROUGH CASE STUDIES - Kavya Singh. Dr. Bhargavi D Hemmige (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This research delves into the changing interplay between social media platforms and contemporary social movements, aiming to reveal the multifaceted impact of digital communication on mobilization, organization, and ultimate results. Employing a case study approach, the study investigates prominent social movements across diverse geographical and socio-political contexts, analysing how social media platforms shape and influence the path of these movements. The research unfolds by examining the role of social media in the mobilization phase, exploring how online platforms serve as medium for collective action, enabling rapid dissemination of information, fostering solidarity, and amplifying the voices of marginalized groups. Also, the study scrutinizes the organizational dynamics facilitated by social media, scrutinizing the mechanisms through which these platforms contribute to the coordination of activities, resource mobilization, and the establishment of networks that transcend traditional boundaries. Moving beyond the mobilization and organization phases, the research critically evaluates the outcomes of social movements in the digital era. It considers the extent to which social media influences the effectiveness and sustainability of these movements, assessing both the positive and negative consequences. The study also addresses the challenges and ethical considerations associated with the reliance on digital platforms for activism, including issues of misinformation, surveillance, and platform censorship. By synthesizing insights from diverse case studies, this research aims to contribute a nuanced understanding of the intricate relationship between social media and social movements. It provides valuable insights for scholars, activists, and policymakers seeking to comprehend the evolving landscape of contemporary activism in an increasingly digitalized world.